The recent concept in the management of anterior Skull base tumor: A review of the literature - Sigdel, Brihaspati; Neupane, Bhima; Panta, Ashirbad (Journal of Brain and Spine Foundation Nepal, 2021)
Introduction Tumor of the skull base are classified based on their tissue of origin. Tumor originates from epithelium, mesenchyme, and neuroectoderm. Management of tumors depends on location, histologic characteristics, and their behaviors. A sinus endoscopy, Computerized tomography scan, and Magnetic Resonance Imaging should be performed to know the type and extent of the tumor. Treatment includes surgical excision either endoscopic vs open, chemotherapy and immunotherapy. We are highlighting the management option of each tumor according to their type of tissue origin and its location. Methods: A PubMed search was conducted for relevant publications using the terms “anterior skull base malignancies” and “anterior skull base malignancies treatment and “open vs endoscopic anterior skull base malignancies.” The publication language should be English. Results: Articles published after 2000 that cover the most recent paradigm shift in the treatment of anterior skull base tumors were included. There have been 35 articles found, despite 20 of them are being rejected due to the lack of full text, abstract, and non-english. Three of the fifteen articles have been downloaded twice, thus they have been excluded. Conclusion: Skull base tumors are treated based on findings of diagnostic nasal endoscopy and imaging results. CT scans and MRIs are becoming more significant in the diagnosis of diseases. Endoscopic techniques to the skull base were beneficial in treating the malignancy. Chemotherapy can be used as a gold standard first-line treatment with radiation and surgery for significant types of head and neck tumors. immunotherapy-like checkpoint inhibitors targeting PD1 are the second-line treatments of advanced HNSCC. Prospective research and trials will be required in the future.